RAndomised controlled trial to imProve depressIon and the quality of life of people with Dementia using cognitive bias modification: RAPID study protocol. Issue 7 (23rd July 2014) - Almeida, Osvaldo P; MacLeod, Colin; Flicker, Leon; Ford, Andrew; Grafton, Ben; Etherton-Beer, Christopher
Abstract : Introduction: Depressive symptoms are common and undermine the quality of life of people with Alzheimer's disease (AD). Cholinesterase inhibitors and antidepressants have all but no effect on the mood of patients, and their use increases adverse events. Cognitive bias modification (CBM) targets attentional and interpretative biases associated with anxiety, dysphoria and depression and may be useful to treat depression in AD (DAD). This trial aims to determine the effect of CBM on depression scores and the quality of life of people with DAD. Methods and analysis: Randomised, double-blind, parallel, controlled trial of CBM (1:1 allocation ratio). Participants will be 80 adults with probable AD living in the Western Australian community who score 8 or more on the Cornell Scale for Depression in Dementia (CSDD). They will have mild to moderate dementia (Mini-Mental State Examination—MMSE score ≥15) and will be free of severe sensory impairment or suicidal intent. The intervention will consist of 10 40 min sessions of CBM delivered over 2 weeks using a high-resolution monitor using a local computer station at the Western Australian Centre for Health and Ageing. The primary outcomes of interest are the 2-week change, from baseline, in the severity of CSDD scores and the Quality of Life AD (QoL-AD) scores. Secondary outcomes include changes in the CSDD, QoL-AD after 12 weeks, and changes in MMSE scores, negative attentional and interpretative bias and the proportion of participants with CSDD <8 after 2 and 12 weeks. Ethics and dissemination: The study will comply with the principles of the Declaration of Helsinki and participants will provide written informed consent. The Ethics Committee of the Royal Perth Hospital will approve and oversee the study (REG14-036). The results of this trial will provide level 2 evidence of efficacy for CBM as a treatment of DAD. Trial registration number: Australian and New Zealand Clinical Trials Registry number ACTRN12614000420640, date registered 06/04/2014.